De-radicalisation programmes : changing minds? - Mohamed Ali (2009)
A de-radicalisation or rehabilitation programme is an important and effective strategy to combat the current wave of terrorism and extremism. Several countries have developed such programmes to eliminate the ideology that has been rooted in the minds and hearts of the extremists and replace it with positive ones.